Predicted changes in distribution and richness of wild edible plants under climate change scenarios in northwestern Kenya - Oluoch, Wyclife Agumba; Borgemeister, Christian; de Deus Vidal Jr, João; Fremout, Tobias; Gaisberger, Hannes; Whitney, Cory; Schmitt, Christine B. (Springer, 2024)
Wild edible plants (WEPs) can provide diverse and nutrient-rich food sources that contribute to the health and well-being of communities worldwide. In northwestern Kenya, WEPs are vital dietary components for nomadic pastoral communities with limited access to diverse cultivated food crops. However, the increasing impact of climate change poses a threat to these valuable food resources, and their sustainable utilization remains precarious. Here, we assessed the potentially suitable habitats and richness of 23 selected WEPs in the region using a species distribution modeling (SDM) approach. We used species occurrence points from global databases, a national herbarium, and field surveys and made predictions spanning two future time intervals, 2041–2070 and 2071–2100, across three shared socioeconomic pathways (126, 370, and 585) using bioclimatic variables from five global circulation models. We also included soil and topographic variables in our models. We calibrated maximum entropy models using individually tuned parameters. Our future predictions showed a predominant decline in habitat suitability for half the studied WEPs. The richness of the selected WEPs are predicted to remain rather stable under projected future climates concentrating in southern parts of Turkana County. Conservation and management measures need to consider the changing availability of these valuable resources in order to underpin the dietary diversification of local communities.